THE INDIGENOUS PEOPLES RIGHTS INCLUDED IN THE PERUVIAN NATIONAL HUMAN RIGHTS PLAN 2018-2021 - Rodríguez Gómez, Edgardo (2020)
The article analyzes the inclusion of indigenous peoples as one of the special protection groups in the National Human Rights Plan 2018-2021, whose implementation is on charge of the Peruvian Ministry of Justice and Human Rights. The main thesis is that strategic actions and indicators related to the situation of indigenous peoples responded both to a results-based management model that priories some issues, as well as to the international human rights standards. Those where established by Convention 169 of the International Organization of Labor, the jurisprudence of the Inter-American Court of Human Rights, and the recommendations given by the Inter-American Commission on Human Rights. It also takes into account the criteria and guidelines given by the United Nations Special Rapporteur on the situation of human rights and fundamental freedoms of indigenous people.National Human Rights Plan 2018-2021 - public policy and human rights - indigenous peoples - special protection groups - results-based management